Dialysis treatment in children with amyloidosis due to juvenile rheumatoid arthritis - Sieniawska, Maria; Roszkowska Blaim, Maria; Wojciechowska, Beata (The Turkish Journal of Pediatrics, 1996)
Rapid deterioration of renal function in amyloidotic children may be due to progression of amyloidosis or exacerbation of chronic renal failure (CRF). Continuous ambulatory peritoneal dialysis (CAPD) is superior to hemodialysis (HD) both in end-stage renal disease and in exacerbations of CRF in amyloidosis. A better supply of protein and easier control of hypertension are possible on CAPD, while HD is associated with the risk of hypovolemia episodes, cardiovascular disturbances and bleeding connected with heparinization.